2019
DOI: 10.1021/acsnano.9b05650
|View full text |Cite
|
Sign up to set email alerts
|

Counterion-Dependent Mechanisms of DNA Origami Nanostructure Stabilization Revealed by Atomistic Molecular Simulation

Abstract: The DNA origami technique has proven to have tremendous potential for therapeutic and diagnostic applications like drug delivery, but the relatively low concentrations of cations in physiological fluids cause destabilization and degradation of DNA origami constructs preventing in vivo applications. To reveal the mechanisms behind DNA origami stabilization by cations, we performed atomistic molecular dynamics simulations of a DNA origami rectangle in aqueous solvent with varying concentrations of magnesium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 80 publications
2
38
0
4
Order By: Relevance
“…For cationic species other than metal ions, their interaction mechanisms with DNA are rarely reported. Markvoort et al simulated the interaction model between a series of small molecules and DNA nanostructures [ 38 ]. Larger molecules, such as peptides, mainly interacted with the phosphate backbone with one duplex or between two DNA duplexes.…”
Section: Resultsmentioning
confidence: 99%
“…For cationic species other than metal ions, their interaction mechanisms with DNA are rarely reported. Markvoort et al simulated the interaction model between a series of small molecules and DNA nanostructures [ 38 ]. Larger molecules, such as peptides, mainly interacted with the phosphate backbone with one duplex or between two DNA duplexes.…”
Section: Resultsmentioning
confidence: 99%
“…[94,95] This is due to ion-specific differences in the type of interaction, binding site,a nd binding affinity between DNAa nd the individual ion species. [94,96] Recently,R oodhuizen et al performed atomistic molecular-dynamics simulations of DO stabilization by various cations. [96] They found that Mg 2+ ions bind strongly to minor-groove atoms and the backbone phosphates,whereas Na + binding is much weaker and barely involves the phosphates.T his strong binding of the Mg 2+ ions is responsible for the somewhat surprising observation that DO assembled in aM g 2+ -containing buffer can be gently transferred into Mg 2+ -free buffers and even pure water without al oss of integrity.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…[94,95] Dies liegt an ionenspezifischen Unterschieden in der Art der Interaktion, der Bindungsstelle und der Bindungsaffinitätz wischen der DNAu nd der jeweiligen Ionenspezies. [94,96] Roodhuizen et al führten vor kurzem atomistische Moleküldynamiksimulationen der DO-Stabilisierung durch verschiedene Kationen durch. [96] Sie fanden, dass Mg 2+ -Ionen stark an Atome der kleinen Furche und die Phosphate des Rückgrats binden, wohingegen die Na + -Bindung viel schwächer ist und die Phosphate kaum involviert.…”
Section: Angewandte Chemieunclassified
“…Roodhuizen et al. führten vor kurzem atomistische Moleküldynamiksimulationen der DO‐Stabilisierung durch verschiedene Kationen durch . Sie fanden, dass Mg 2+ ‐Ionen stark an Atome der kleinen Furche und die Phosphate des Rückgrats binden, wohingegen die Na + ‐Bindung viel schwächer ist und die Phosphate kaum involviert.…”
Section: Herausforderungen Für Die Anwendung Von Dna‐nanostrukturen Iunclassified